2015
DOI: 10.1007/s12032-015-0635-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of postoperative radiotherapy concurrent with S-1 in patients with gastric cancer

Abstract: Postoperative chemoradiotherapy (CRT) with concurrent 5-fluorouracil is the standard care for gastric cancer patients after curative surgery. The previous studies revealed that the subgroup of patients with high recurrence risk would benefit most from adjuvant CRT. S-1, a novel oral fluorouracil, has showed very effective in metastatic gastric cancer and became the standard option for gastric cancer with D2 dissection. The safety and dosage of S-1 combined with postoperative radiotherapy have not yet been eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Besides, the specific standard initiation time, duration and dosage of chemotherapeutic agents and radiotherapy were based on our previous trials design. [ 7 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the specific standard initiation time, duration and dosage of chemotherapeutic agents and radiotherapy were based on our previous trials design. [ 7 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…A preclinical study suggested that S-1 enhanced sensitivity to radiotherapy [21]. In clinical settings, moreover, the feasibility and efficacy of radiotherapy concurrent with S-1 were demonstrated in some cancers including oral [6], esophageal [22], and gastric cancer [23]. For these reasons, we selected S-1 as a substitute.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this drug is not available in Western countries. In some recent studies, S-1 was administered concomitantly to RT, alone[ 48 - 50 ] or in combination with cisplatin, both in a preoperative and postoperative setting[ 51 , 52 ]. No excessive toxicities and encouraging outcomes were reported, and an MTD ranging between 70 and 80 mg/m 2 was identified.…”
Section: Recent Evidence Of Novel Chemotherapeutic Regimens and Modermentioning
confidence: 99%